A Study of Radiation Dose to Staff and Close Contacts from Patients Undergoing Left Ventricular Function Assessment Using [99mTc]-labeled Red Blood Cells - Poonak, Kanokon; Chochai, Peerawan; Tepkleang, Jeerarat; Thinkam, Witchayaporn (Srinagarind Medical Journal, 2025)
Background and objectives: The assessment of cardiac function through the measurement of left ventricular ejection fraction (LVEF) using the multiple gated acquisition (MUGA) scan technique is recognized for its high accuracy and reproducibility. However, this procedure requires the intravenous administration of a radiopharmaceutical agent, resulting in radiation emission from the patient, which could potentially affect medical personnel. The objective of this study was to quantify the radiation dose from patients undergoing MUGA scans at varying time intervals post-radiopharmaceutical injection and distances from the patient. Additionally, the study sought to estimate the radiation exposure of radiology technologists, radiology assistants, and individuals in close contacts to the patient. Methods: A prospective descriptive study was conducted on a sample of 20 patients who underwent MUGA scans at the Nuclear Medicine Department of Vajira Hospital. Radiation dose measurements were performed using a survey meter placed at the epigastric level at two time points: immediately after radiopharmaceutical injection and 40 minutes post-injection. Measurements were taken at distances of 0.25, 0.50, 1.00, and 2.00 meters from the patients. The estimated radiation doses received by radiologic technologists, radiology assistants, and individuals in close contact with the patients were subsequently calculated and compared to the radiation dose limits per year recommended by the International Commission on Radiological Protection (ICRP). Results: The mean radiation doses emitted from patients immediately after injection at distances of 0.25, 0.50, 1.00, and 2.00 meters were 60.65 ± 16.08, 27.53 ± 4.38, 11.20 ± 1.52 and 3.84 ± 0.89 microSieverts/hour (µSv/hr), respectively. At 40 minutes post-injection, the mean radiation doses decreased to 53.53 ± 16.60, 25.36 ± 4.52, 10.07 ± 1.33 and 3.30 ± 0.57 µSv/hr at distances of 0.25, 0.50, 1.00 and 2.00 meters, respectively. The estimated radiation doses received by radiological technologists, radiology assistants, and individuals in close contacts to the patient at a distance of 0.25 meters were 3.90 ± 3.03, 2.59 ± 1.67, and 38.93 ± 25.08 µSv, respectively. Conclusion: The findings indicate an inverse relationship between the radiation dose emitted from patients and both distance from the patient and elapsed time post-injection. The radiation doses received by occupational workers and individuals in close proximity to the patients remained below the recommended dose limits established by ICRP.